Design of a porous material with isotropic negative Poisson's ratio. (June 2016) - Carta, Giorgio; Brun, Michele; Baldi, Antonio
Highlights: We propose the design of an isotropic porous structure with negative Poisson's ratio. Isotropy is due to the threefold symmetry of the arrangement of the voids. Poisson's ratio is determined experimentally through Digital Image Correlation. The experimental findings match very well with the results of numerical simulations. Periodic analysis is employed to determine the effective properties of the structure. Abstract: This paper proposes the design of a two-dimensional porous solid with omni-directional negative Poisson's ratio. The hexagonal periodic distribution of the pores makes the effective behavior isotropic. Both experimental tests and numerical simulations have been performed to determine the effective properties of the porous solid. A parametric study on the effect of the geometrical microstructural parameters is also presented. This auxetic structure is easy to fabricate and can be very useful in several engineering applications.